A Study on Recovery Rate, Storage Loss Rate and Recovery Cycle of Chinese Paper Products Based on Kyock Model. (17th February 2021) - Zhao, Xiaodi; Diao, Gang; Ma, Kun; Li, Zhen
ABSTRACT: The recovery rate of paper products is a key factor in measuring the recyscling potential and the sustainability of the paper industry. Accurately measuring the recovery rate of paper products holds important theoretical and practical value. This paper took the non-recycling part and time factor into account and built the Koyck model to estimate the recovery rate, storage loss rate and recovery cycle of paper products. The model results showed that the recovery rate of Chinese paper products in 2017 increased to 58.05%, which was 10% higher than the results of methods that did not contain the non-recycling part or the time factor. The model results also showed that the storage loss rate of Chinese paper products was much higher than that of developed countries while the recovery cycle was close to the level of developed countries. The distribution analysis showed that the storage loss rate and recovery cycle of Chinese paper products varied significantly over time, which may be the result of policies and the change of consumption structure. It is suggested that the Chinese government should take measures to reduce the storage loss rate of paper products and enhance their recycling ability to achieve sustainable development.